NADH fluorescence lifetime is an endogenous reporter of α‐synuclein aggregation in live cells. Issue 6 (24th February 2015) - Plotegher, Nicoletta; Stringari, Chiara; Jahid, Sohail; Veronesi, Marina; Girotto, Stefania; Gratton, Enrico; Bubacco, Luigi
ABSTRACT: α‐Synuclein (aS) aggregation has been amply investigated for its involvement in Parkinson's disease because its amyloid fibrils are the main constituent of Lewy bodies, one of the hallmarks of the disease. aS aggregation was studied here in vitro and in cellular models to correlate aggregation products with toxicity mechanisms. Independent results published elsewhere suggested that aS overexpression and/or aggregation may impair cellular metabolism and cause mitochondrial damage. In this context, we report the characterization of changes in NADH fluorescence properties in vitro and in human embryonic kidney 293 cells upon aS aggregation. The application of the phasor approach to study NADH fluorescence lifetime and emission allowed us to identify changes that correlate with aS aggregation. In particular, the fraction of bound NADH, characterized by longer lifetimes in comparison to free NADH, is increased, and the maximum of the NADH emission is shifted toward shorter wavelengths in the presence of aggregating aS both in vitro and in cells. These data suggest that NADH binds to aggregated aS. NMR experiments in vitro substantiate such binding, which occurs during aggregation. NADH fluorescence is thus useful to detect aS aggregation and by extension the associated oxidative stress.—Plotegher, N., Stringari, C., Jahid, S., Veronesi, M., Girotto, S., Gratton, E., Bubacco, L. NADH fluorescence lifetime is an endogenous reporter of α‐synuclein aggregation in live cells. FASEB J. 29, 2484‐2494 (2015). www.fasebj.org